Kajian Penerapan Arsitektur Post-Modern pada Museum KH. Asyim Asy’ari di Jombang - Baidhowi, Muhammad Faiz; Paryoko, Vijar Galax Putra Jagat (Universitas Medan Area, 2025)
KH Museum Hasyim Asy'ari in Jombang is an important building dedicated to commemorating the cultural and historical heritage of KH. Hasyim Asy'ari, a very influential religious and educational figure in Jombang, East Java. KH Museum Hasyim Asy'ari is an architectural project that uses a postmodern approach to depict the history and intellectual heritage of prominent religious figures in Jombang. Through research on the KH museum building. Hasyim Asy'ari, can increase our insight into the design of Islamic buildings in Jombang and to find out the characteristics of existing post-modern architectural buildings. This research uses a qualitative research method, namely by collecting data through library techniques. The museum's design combines traditional Javanese elements with contemporary geometry and postmodern ornamentation. This is related to the postmodern architectural approach for the KH museum. Hasyim Asy'ari is very suitable for further study. Apart from that, this research will explore the use of space in the museum, such as the layout of exhibition galleries, information rooms and meeting rooms. So, this aims to understand how the space is used to display historical objects and information related to the life and works of KH. Hasyim Asy, Ari. Apart from that, the roof of the KH museum. Hasyim Asy'ari has a symbol for the kiai and santri, which symbolizes the santri who submit to the kiai.